Beitrag zur Entwicklung von Konstantflusspumpen für Frischbeton unter genauerer Betrachtung der Dickstoffventile - Weber, Felix (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2021)
On almost every construction site, mobile fresh-concrete pumps of different designs can be found, all of which have an interruptions in delivery. In this work, a fresh-concrete constant-flow pump is developed and simulated. In order to be able to develop the new type of fresh-concrete valve required for this, knowledge is built up in a first step. This is done with a test bench using statistical design of experiments.